Development of Chrysanthemum Drying Process for the Sa-Ngo Royal Project Development Center, Chiang Rai Province - Assawarachan, Rittichai; Tantikul, Samerkhwan; Boonlow, Boontham; Arwastprom, Udorn; Thongkrajang, Pannumast (Area Based Development Research Journal, 2021)
Chrysanthemum flower (Chrysanthemum indicum Linn) cultivation is the main occupation of farmers in the area of ​​Sri Don Mun subdistrict, Chiang Rai province, Thailand. The flowers are harvested and sold to the Sa-Ngo Royal Project Development Center for the drying process. However, the previously-used dryers were unable to dry the flowers in time, resulting in a spoiled product. This research project aims to develop an efficient drying process and drying plants for the Sa-Ngo Royal Project Development Center to comply with the safety standards at the level of community enterprises to support flowers product from the farmers. The result showed that after the improvement of the dryer, the upgraded dryer had a drying rate of 0.127 (gwater/gdry matter)* min, the rate of return (ROR) was 206.61% per year, and the break-even point (BP) of the cost was 6 months. The selling income of fresh chrysanthemums flower increased from 42.50 to 47 baht per kg. As a result, the higher purchasing price of harvested materials had welcomed more farmers to join the program from 10 to 250 families, projecting a total income of over 5.85 million baht in 2020. In conclusion, this subsidy guidance follows the policy of promoting the sustainability of the Royal Project Development Center and strengthens the center as a revenue-generating source for local farmers according to the sufficiency economy philosophy.